Activation of buried p-GaN through nanopipes in large-size GaN-based tunnel junction LEDs. (4th May 2021) - Yan, Shumeng; Feng, Meixin; Fan, Shizhao; Zhou, Rui; Tang, Yongjun; Jiang, Tianhao; Liu, Jianxun; Zhou, Yu; Sun, Qian; Yang, Hui
Abstract: In GaN-based light-emitting diodes (LEDs), tunnel junctions offer a way of replacing the highly resistive p-type GaN (p-GaN) ohmic contact with a low-resistance n-GaN ohmic contact. However, the p-GaN would be re-passivated by hydrogen atoms during the subsequent growth of n-GaN in a metal-organic chemical vapor deposition (MOCVD) chamber. The n-GaN layer, acting as a hydrogen diffusion barrier, hinders the thermal activation of the underlying p-GaN. Here, we report a method to thermally activate the buried p-GaN in tunnel junction LED (TJ-LED) through vertically aligned nanopipe arrays across the top n-GaN layer, which provides a hydrogen outgassing passage. The fabrication of nanopipes is realized via inductive coupled plasma etching using a mask prepared by self-assembled nanosphere arrays. As a result, we attain large-size TJ-LED chips, exhibiting nearly equivalent p-GaN activation and superior light extraction compared to conventional LEDs. Specifically, the light extraction efficiency is boosted by 44% relative to conventional LEDs at an injection current density of 100 A cm −2 .